2011
DOI: 10.1007/s00421-011-2195-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen breathing or recompression during decompression from nitrox dives with a rebreather: effects on intravascular bubble burden and ramifications for decompression profiles

Abstract: Preventive measures to reduce the risk of decompression sickness can involve several procedures such as oxygen breathing during in-water decompression. Theoretical predictions also suggest that brief periods of recompression during the course of decompression could be a method for controlling bubble formation. The aim of this study was to get clearer information about the effects of different experimental ascent profiles (EAPs) on bubble reduction, using pure oxygen or recompression during decompression for ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…Hence, any oxygen window effect of EAN versus compressed air breathing was less pronounced (inspired O 2 pressures of 1.04 vs. 0.59 atm and N 2 partial pressures of 2.21 vs. 2.21 atm, respectively) than in our study (inspired O 2 pressures of 1.37 atm vs. 0.79 and inspired N 2 partial pressures of 2.43 vs. 3 atm). Thus, our findings are in good agreement with important role of the O 2 suggested by Blatteau et al: increasing the FiO 2 from 0.4 to 1.0 at 10 msw during the final part of the decompression from a simulated dry chamber dive markedly reduces venous bubble formation [ 5 ]. However, breathing a single gas mixture during an entire dive profile is more practical for divers than changing gas mixtures during ascent.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, any oxygen window effect of EAN versus compressed air breathing was less pronounced (inspired O 2 pressures of 1.04 vs. 0.59 atm and N 2 partial pressures of 2.21 vs. 2.21 atm, respectively) than in our study (inspired O 2 pressures of 1.37 atm vs. 0.79 and inspired N 2 partial pressures of 2.43 vs. 3 atm). Thus, our findings are in good agreement with important role of the O 2 suggested by Blatteau et al: increasing the FiO 2 from 0.4 to 1.0 at 10 msw during the final part of the decompression from a simulated dry chamber dive markedly reduces venous bubble formation [ 5 ]. However, breathing a single gas mixture during an entire dive profile is more practical for divers than changing gas mixtures during ascent.…”
Section: Discussionsupporting
confidence: 92%
“…Theoretically, higher blood and tissue oxygen partial pressures should lead to increased nitrogen dissolution and subsequent clearance from the body. Indeed, increasing the FiO 2 from 0.4 to 1.0 during the ascent from dives, in which a rebreather circuit (closed circuit) was used, led to reduced intravascular bubble scores, demonstrating the relevance of the oxygen window during decompression [ 5 ]. Currently, in addition to reduced decompression times, gas mixtures with increased FiO 2 (enriched air nitrox, EAN) are frequently used to improve diving safety.…”
Section: Introductionmentioning
confidence: 99%
“…48 h or more) allowing complete gas equilibration (saturation), but rather a 12 h exposure expected to saturate most, but not all, compartments (sub-saturation). However, we used a mathematical model (BORA model, BF systemes) to simulate and predict bubble formation for extended exposure [12], [13]. Under conditions of saturation diving, compartments controlling decompression rate are very slow in terms of gas exchange.…”
Section: Methodsmentioning
confidence: 99%
“…However, the true risk of DCS associated with cave diving is diffi cult to estimate with certainty, and it is not clear if this argument is a strong one. In contrast to the calculations by Gernhardt and the animal trial of Møllerløkken, a recent human study by Blatteau et al has not shown benefi cial eff ects of a single recompression from 3 to 9 m lasting 5 min after a 25 min dive in a wet recompression chamber [ 4 ] . Possible reasons for the lack of benefi t are the small sample size (N = 8) or the fact that only one single recompression was performed in contrast to the multiple recompressions after multiple decompression stops in the previous studies.…”
Section: Bubble Formationmentioning
confidence: 95%
“…Previous theoretical calculations of bubble growth after saturation dives also postulated an advantage of intermittent recompression during the decompression procedure [ 13 ] . A single recompression lasting 5 min during decompression has recently been reported not to reduce bubble formation [ 4 ] . However, it remains unclear whether multiple recompressions after a longer SCUBA dive are superior to conventional decompression schedules.…”
Section: Eff Ects Of Flirt On Bubble Growth In Manmentioning
confidence: 99%